PENGEMBANGAN DAKWAH JAMA’AH MASTURAT DALAM MEMBINA RUMAH TANGGA SAKINAH DI KOTA PALU - Ibrahim Latepo; Suharto Suharto (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2014)
Happy family is a dream for every Muslim. This kind of family is often associated with harmonious and peaceful family. Islam as a religion brings perfect teachings which contain instructions that guide individuals to be good, civilized, and having good quality. To achieve this, continuous and comprehensive da’wah efforts are needed. Preaching is a very noble task because it leads to the goal of reaching the divine blessing, as performed by the Masturat group in their da’wah activities in Palu. This da’wah activities focused on the effort to restore women to their nature in the household, whose its goal is to build happy family.